2016
DOI: 10.1016/j.jmb.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The Spliceosomal Protein SF3B5 is a Novel Component of Drosophila SAGA that Functions in Gene Expression Independent of Splicing

Abstract: The interaction between splicing factors and the transcriptional machinery provides an intriguing link between the coupled processes of transcription and splicing. Here, we show that two components of the SF3B complex that forms part of the U2 small nuclear ribonucleoprotein particle (snRNP), SF3B3 and SF3B5, are also subunits of the Spt-Ada-Gcn5 acetyltransferase (SAGA) transcriptional coactivator complex in Drosophila melanogaster. Whereas SF3B3 had previously been identified as a human SAGA subunit, SF3B5 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 79 publications
2
24
0
Order By: Relevance
“…Indeed, dynamic acetylation of an H3K4me3 nucleosome positioned on exon 2 of MCL1 is linked to alternative skipping of this SF3B1-regulated exon 60 , 61 . SF3B complex components have been also found associated with the epigenetic remodeling complexes Polycomb and SAGA 62 64 , adding yet another layer of regulatory functions that can be affected by SF3B1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, dynamic acetylation of an H3K4me3 nucleosome positioned on exon 2 of MCL1 is linked to alternative skipping of this SF3B1-regulated exon 60 , 61 . SF3B complex components have been also found associated with the epigenetic remodeling complexes Polycomb and SAGA 62 64 , adding yet another layer of regulatory functions that can be affected by SF3B1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Tandem FLAG-HA affinity purification and MudPIT analysis was conducted from stable Drosophila S2 cell lines as described previously (Stegeman et al, 2016). TAP purifications from S. cerevisiae was performed as described previously (Lee et al, 2004).…”
Section: Affinity Purification Mudpit Analysis and Histone Acetyltramentioning
confidence: 99%
“…Briefly, shared spectral counts (sSpC) were distributed based on spectral counts unique to each protein (uSpC). Histone acetyltransferase assays were performed as previously described (Stegeman et al, 2016) using Flag-purified complexes and HeLa core histones or human histone H3 peptide (K5-K23) as substrate.…”
Section: Affinity Purification Mudpit Analysis and Histone Acetyltramentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, SF3b5 was additionally identified as a SAGA component together with the above SF3b3, based on an interaction with the conserved Sgf29 subunit of the human SAGA complex [98]. Moreover, a recent study showed that SF3b3 and SF3b5 were also found in drosophila SAGA [99]. This suggests that these two proteins may be intrinsic components of SAGA in higher eukaryotes.…”
Section: Sf3b Components In the Nucleusmentioning
confidence: 98%